Regulation and function of the Streptomyces plasmid pSN22 genes involved in pock formation and inviability. - Kataoka, M (1991)
pSN22 is an 11-kb multicopy plasmid from Streptomyces nigrifaciens which is being studied in Streptomyces lividans. A segment of about 7 kb of pSN22 contains five genes involved in conjugation. Three of them, traA, traB, and traR, are essential for plasmid transfer and for the mobilization of chromosomal markers (fertility), while the remaining two genes, spdA and spdB, merely enhance the efficiency of plasmid transfer, resulting in the formation of larger pocks. In vitro promoter-probing experiments identified a 550-bp BglII-SmaI DNA fragment with promoter activity in both orientations; Northern (RNA blot) hybridization identified corresponding divergent transcripts of 1 and 5.2 kb for traR and the traA-traB-spdB operon, respectively. The traR gene product repressed its own transcription and also the transcription of the traA-traB-spdB operon. Plasmids containing a functional traB gene could not "survive" without traR being present in the same cell either in cis or in trans, presumably because unregulated expression of traB is lethal to the host. Plasmids with a functional traA gene but without traR had a low transformation efficiency and inhibited the growth of host cells.